Radio control of radiation from radio electronic devices. Problems and solutions - Bezruk, V.M.; Holoborodko, Y.M.; Zabolotnyi, V.I.; Skybenko, M.S. (Radiotekhnika, 2025)
This article analyzes the challenges of radio monitoring in the decameter band, which is crucial for ensuring reliable radio communications. It highlights key issues stemming from the propagation characteristics of decameter waves (surface and sky waves), leading to high spectrum congestion and making it difficult to detect target radio emissions (RE). The drawbacks of existing manual and visual-instrumental monitoring methods are examined, characterized by low speed and an inability to effectively detect short-duration signals. An approach to automating radio monitoring is proposed, utilizing a priori information about radio emissions, specifically their polarization characteristics, carrier frequency, and source location zone. The effectiveness of «thinning» the stream of analyzed signals is substantiated, allowing for a significant reduction in the number of channels requiring detailed analysis. It is shown that automatic selection of far-zone emissions can reduce the scanning time of the band by tens or hundreds of times. The problem of multi-alternative detection of specified signals under conditions of a priori uncertainty is considered, along with the importance of using onboard computing resources for the flexibility and adaptability of radio monitoring systems. The research results confirm the possibility of significantly improving the speed and quality of decameter band radio monitoring through the implementation of the proposed methods.